EDUCAÇÃO DO MST E A PROPOSTA CURRICULAR EM CIÊNCIAS DA NATUREZA: A EXPERIÊNCIA DA ESCOLA ESTADUAL DE ENSINO FUNDAMENTAL XIII DE SETEMBRO, SÃO MATEUS - ES - Souza, Aleilda Ouverney de (2022)
The major goal of this study is to examine the relationship between the curriculum organization in the field of natural sciences and the pedagogical practices in schools in MST’s settlements, based on the training process of educators from Agrarian Reform Settlements. To achieve this goal, the analysis begins with the reality of the XIII de Setembro school, in the Córrego da Areia settlement, municipality of São Mateus - ES, whose curriculum is proposed by the MST State Education Sector, and, thus, enters the divergences and convergences in relation to the official curriculum of the state of Espírito Santo, based on the pedagogical experiences lived at school. This is a discussion that stems from a number of critical concerns aimed at improving the practice of educators in settlement schools in areas of agrarian reform, particularly in the field of natural sciences, and culminate in the following objectives: Examine the curriculum dimension in the several theoretical perspectives to interpret the historical process of curriculum development in the school from its Political Pedagogical Project; learn the connection between the curriculum in the area of natural sciences and the pedagogical practice in the investigated school; confront the curriculum policies of the state of Espírito Santo and the curriculum proposal for rural education; debate the modifications that have occurred in the official curriculum of the state of Espírito Santo, in the area of natural sciences, for the assistance in rural schools in the face of the pandemic. Searching for possible answers, the study was based on the methodological procedure of action-research, rescuing documents and interviewing research participants, having as a theoretical reference author who have dedicated themselves to the study of rural education in recent decades. An approximation was also made between the reality of settlement schools and the theoretical bases of ethnoculum and ethnolearning, seeking to show that alternative curricular proposals to the official one is not only possible, but also desirable. Finally, it is hoped that this study can contribute to the debate on curricular policies aimed at schools in settlements in the state of Espírito Santo.